School and community factors involved in Chilean students’ perception of school safety - López, Verónica; Torres-Vallejos, Javier; Villalobos-Parada, Boris; Gilreath, Tamika D; Ascorra, Paula; Bilbao, Ángeles; Morales, Macarena; Carrasco-Aguilar, Claudia (Wiley, 2017)
Identifying and understanding predictors of school safety perceptions is important due to its consequences for students. However, it is not clear what school-related factors most contribute to explaining students’ perception of school safety, and how they relate to community-related factors such as neighborhood safety. The purpose of this study was to understand the factors associated with Chilean elementary and middle school students’ perceptions of school safety. We used a sample of 5,455 students from low socioeconomic status public schools, and analyzed the predictive value of peer physical and verbal victimization; teacher and school staff victimization; teacher's social support; and perception of safety in the students’ neighborhoods on perceptions of school safety. Findings showed that although different forms of school violence, particularly peer physical victimization and physical and sexual victimization from teachers and school staff, contribute to students’ perception of school safety, the highest contribution came from students perceiving their neighborhoods as unsafe. In contrast, teacher social support contributed to increased levels of perceived school safety. We discuss the need for school-based interventions that address physical victimization and engage teachers in prosocial and less punitive approaches to foster a positive and safe school climate, and in fostering school–community partnerships.
https://openpolicyfinder.jisc.ac.uk/id/publication/15235?from=single_hit
Keywords: Centros docentes - Medidas de seguridad; Mediación escolar; Violencia en la escuela; Community; School climate; School safety; School violence; Students